A review: non-antibacterial, non-antifungal and non-anticancer properties of nanoparticles the forgotten paradigm. (17th February 2021) - Ankamwar (NanoBA), Balaprasad; Yadwade, Rachana
Abstract: The review highlights the need of non-antibacterial, non-antifungal and non-anticancer characters of metal or metal oxide nanoparticles. The usage of nanoparticles as a part of therapeutic measures results in certain unfavourable effects. The nanoparticles can disturb healthy gut microorganisms that may bring about some health damages regarding pathogenic diseases, obesity, and inflammation likewise. Even the nonspecific interactions of nanoparticles with healthy cells and tissues can cause altered expressions of various pro-inflammatory factors and stress related genes. This review indicates and prospect about the demand of nanoparticles with non-antibacterial, non-antifungal and non-anticancer properties. Such nanoparticles will be effective in various remedial and diagnostic purposes.